EVALUASI IMPLEMENTASI ASESMEN AUTENTIK DALAM PEMBELAJARAN MATEMATIKA DI SMP NEGERI 1 CIKIDANG KABUPATEN SUKABUMI - Rani Nurhayati Rosida; Hendro Prasetyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the implementation of authentic assessment in the math learning process at SMP Negeri 1 Cikidang. Authentic assessment is a type of evaluation that measures students’ ability to apply knowledge and skills in real-life contexts rather than through conventional tests. The research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The results indicate that teachers have begun to implement authentic assessment in alignment with the Merdeka Curriculum, focusing on student competencies, creativity, and critical thinking. However, challenges remain in rubric development, time allocation, and teacher understanding of assessment principles. The study concludes that authentic assessment contributes positively to meaningful learning, yet continuous professional development is needed to optimize its implementation.